ATTITUDE TO NON-PROFIT ORGANIZATIONS IN THE NEW UZBEKISTAN - Kadirova Mamlakat Muminovna (American Journals, 2024)
The evolving landscape for non-profit organizations (NPOs) in Uzbekistan reflects a significant shift towards increased government support and recognition of the vital role these organizations play in social development. Historical constraints from the Soviet era have given way to reforms aimed at enhancing the legal and operational environment for NPOs. Recent government initiatives focus on simplifying registration, providing tax incentives, and promoting civic engagement, allowing NPOs to address pressing social issues such as healthcare, education, and human rights. Despite these advancements, challenges such as funding limitations, bureaucratic hurdles, and public skepticism remain. However, opportunities for growth through international collaboration, digital engagement, and youth involvement are emerging, indicating a promising future for NPOs in Uzbekistan.
Keywords: non-Profit Organizations (NPOs), Uzbekistan, government reforms, civil society, social development, legal framework, bureaucratic challenges, community engagement, funding opportunities, human rights, environmental protection, youth empowerment, gender equality, international collaboration, civic participation, transparency and accountability, national nevelopment strategy, capacity building, public perception, digital engagement.